FENOMENA SOSIAL ANAK TUNGGAL DALAM PENCIPTAAN KOMPOSISI MUSIK NUSANTARA “NYAK TUNGGA” - Ahmad Wanda; Asep Saepul Haris; Nursyirwan Nursyirwan (Pascasarjana Institut Seni Indonesia Padang Panjang, 2020)
This work aims to discuss the phenomenon that occurs in the social life of a single child. The only child is a child with no siblings. Based on the results of observations and research on several children who are reviewed from internal (family) and external (environmental) factors, the fact that they have problems in living life at the age of 6 to 21 years, is called Epifani. Epiphany is a moment or experience whose effect can be positive and negative. The works are attracted to the experiences experienced by the single child, and the works relate to the empirical experience of their own works. The focus of this work is on intimidation, psychological impact and maturity created into three pieces of work. This phenomenon concerns the concept of